Effectiveness of Hepatitis B Vaccination on Various Populations: A Systematic Review - Dewi Ratna Sulistina (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2022)
Introduction: Hepatitis B vaccination is important to protect individuals from Hepatitis B virus (HBV) infection. The aim of this study was to conduct a systematic review of the necessity of Hepatitis B vaccination among humans, especially among infants, children, teenagers, adults, risk groups, and health care workers. Methods: Three databases were used in this study, Scopus, Web of Science, and PubMed. We reported the study using PRISMA-P guidelines. The keywords were used in this study (TITLE-ABS-KEY (vaccine) AND TITLE-ABS-KEY (hepatitis AND b) AND TITLE-ABS-KEY (boost)), and we obtained 275 articles. In the web of science, we used ((ALL=(vaccine)) AND ALL= (Hepatitis B)) AND ALL=(Boost), and we obtained 374 articles. In the PubMed, we used ((Vaccine [MeSH Terms]) AND (Hepatitis b [MeSH Terms])) AND (booster immunization [MeSH Terms]), and we obtained 417 articles. Results: There were 60 articles included in this systematic review. The systematic review results showed that infants, children, and teenagers, as well as adult groups who receive the hepatitis B vaccine, can protect for 5-30 years. Meanwhile, risk group and health care workers were suggested to obtain hepatitis B vaccine booster with low anti-HBsAg titer Conclusion: It needs to conduct anti-HBs Ag titer testing to decide whether they need a hepatitis B vaccination booster. Hepatitis B vaccine booster required for the group with anti-HBs Ag titer less than 10 mIU/mL.